2005
DOI: 10.1002/glia.20235
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine toxicity to oligodendrocyte precursors is mediated by iron

Abstract: Inflammatory processes play a key role in the pathogenesis of a number of common neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD), and multiple sclerosis (MS). Abnormal iron accumulation is frequently noted in these diseases and compelling evidence exists that iron is involved in inflammatory reactions. Histochemical stains for iron repeatedly demonstrate that oligodendrocytes, under normal conditions, stain more prominently than any other cell type in the brain. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 74 publications
(68 reference statements)
4
58
0
Order By: Relevance
“…12,31 In the present study, we confirmed that exposure to low concentrations of TNF-a (10 ng/ml) impairs OPC differentiation, causing an accumulation of early progenitors and reducing the relative amounts of differentiating oligodendrocytes in vitro. This phenomenon was not accompanied by a significant induction of apoptosis, which occurred only when the TNF-a concentration was increased to 100 ng/ml.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…12,31 In the present study, we confirmed that exposure to low concentrations of TNF-a (10 ng/ml) impairs OPC differentiation, causing an accumulation of early progenitors and reducing the relative amounts of differentiating oligodendrocytes in vitro. This phenomenon was not accompanied by a significant induction of apoptosis, which occurred only when the TNF-a concentration was increased to 100 ng/ml.…”
Section: Discussionsupporting
confidence: 83%
“…After 7 days of culture, the OPCs were treated for 24 h with a sublethal concentration of TNF-a, or 10 ng/ml, as suggested in a previous study. 12 Subsequently, the growth factors present within the medium, platelet-derived growth factor (PDGF), and basic fibroblast growth factor (bFGF) (which are fundamental to OPC proliferation), were replaced by the thyroid hormone triiodothyronine (T3) to stimulate cell differentiation. After 5 days, the cells were fixed and immunostained for markers of different stages of oligodendrocyte maturation.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of DFO was also selected to compare to our earlier studies on astrocytes (Robb and Connor, 1998). Calcein, an iron-sensitive dye, was used to determine that the amount of TMHF and DFO used in this study was sufficient to affect the labile iron pool (Zhang et al, 2005).…”
Section: Generation Of Oligodendrocyte Precursor Culturesmentioning
confidence: 99%
“…In addition to ROS, activated microglia secrete cytokines such as TNF-␣ and IL-1␀ that can induce the apoptosis of oligodendrocytes (Zhang et al, 2005;Deng et al, 2008). We have shown that, under hypoxic conditions, iron mediates the release of proinflammatory cytokines TNF-␣ and IL-1␀.…”
Section: Discussionmentioning
confidence: 99%